Linguistic manipulation realised on Hoatiti Facebook political statements and comments: A gricean relevance maxim violation - Brown, Papiso Irene (Journal of Applied Studies in Language, 2025)
Adherence to Grice’s maxims assumes that speakers and writers engaged in a conversation are understandable to both their listeners/readers such that words used do not have ambiguous or overlayed meanings that can be misinterpreted to deviate from the actual intended meanings. This study outlines how interlocutors communicate in digital spaces in cases where either the writer/reader does not fully cooperate in a conversation thus violating the Relevance Maxim in political discussions. The proposed study objective is to assess the degree of relevance in political posts and responses, examining whether followers maintain focus on the topic under discussion, or if they deviate into tangential or irrelevant issues on the Hoatiti Facebook page. Therefore, the study is premised on a qualitative method approach limited to a case study. It comprises of Hoatiti Facebook group page randomly extracted statements n=3 and comments n=5 (3x5) to allow for interaction analysis between the writers and the readers using purposive-convenience sampling. Data is analyzed thematically and inductively. The theoretical undertaking to guide this study is premised on Sperber & Wilson’s theory expounded on the 1985 Relevance theory and built on the Gricean model of pragmatic inference and conversation. The findings of the study revealed various fallacies including ad-hominem, tangential, red-herring, or personal attacks fallacies that violated the relevance maxim. It therefore recommends that for interlocutors to stay informed about a topic they must critically evaluate the statements before responding to contribute and give meaningful insights to the conversations through literacy campaigns to inform them of the importance of relevance in online political conversations.